Ligation of the intersphincteric fistula tract procedure and its modifications - Gendia,Ahmed Mohamed Elsayed Metwalli Ali (2018)
ABSTRACT Purpose: Treatment of anal fistulae is regarded as a challenge due to the diverse nature of this disease and its countless complications. Ligation of the intersphincteric fistula tract procedure and its modifications have been popularized among many surgeons worldwide due to their simplicity and promising outcomes. The main purpose of this article was to conduct a comprehensives review of the published literature on ligation of the intersphincteric fistula tract procedure and its modifications. Method: PubMed, the Cochrane database and Ovid were searched from January 2007 to June 2017. Fully published peer-reviewed studies which applied ligation of the intersphincteric fistula tract procedure and its modifications for the treatment of anal fistulae of cryptogenic origin with follow-up of median 12 months were eligible. Uncompleted studies, case reports, reviews, abstracts, letters, short communication, comments, and studies which did not fulfill inclusion criteria were excluded. The primary outcome was to measure primary healing, overall healing, failure, and recurrence of ligation of the intersphincteric fistula tract procedure and its modifications. Results: Twenty-two studies were identified with only ten studies meeting criteria of inclusion. Original ligation of the intersphincteric fistula tract was performed in five studies with a population of 199 patients while the remaining five studies showed four different modifications of the ligation of the intersphincteric fistula tract with a total number of 147 patients. Both original LIFT and its modifications have promising as well as potentially similar outcomes; primary healing in the original ligation of the intersphincteric fistula tract (73.95%) (95% CI 60.3-85.6) performed less than the modifications (82.3%) (95% CI 64.8-94.7). Overall healing in the original ligation of the intersphincteric fistula tract (78.9%) (95% CI 58.5-93.7) performed relatively less than in the modifications (93.6%) (95% CI 81.4-99.6). Failure in the original ligation of the intersphincteric fistula tract (17.9%) (95% CI 4.9-36.5) performed almost the same as the modifications (17.7%) (95% CI 5.3-35.2). Recurrence in the original ligation of the intersphincteric fistula tract was 9.7% (95% CI 1.7-23.2). However, there was no recurrence in the modifications. Conclusion: Ligation of the intersphincteric fistula tract and its modifications are effective and simple procedures in treating simple anal fistulae, especially high transsphincteric ones. However, more trials should be performed to evaluate its effectiveness regarding complex fistulae.